2015
DOI: 10.5121/ijcsea.2015.5101
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Language Requirements Engineering Approach for MDA

Abstract: A software system for any information system can be developed following a model driven paradigm, in particular MDA (Model Driven Architecture). In this way, models that represent the organizational work are used to produce models that represent the information system. Current software development methods are starting to provide guidelines for the construction of conceptual models, taking as input requirements models. In MDA the CIM (Computation Independent Model) can be used to define the business process mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…In [7] also proposed that first, the initial terms are listed, then the reading and analysis of detailed documents can be used to assign the notion, the behavioral response, the attribute and the method of the recorded words. The eLEL construction process consists of thirteen steps based on the process proposed by [7,11,13]:…”
Section: Elel Building Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In [7] also proposed that first, the initial terms are listed, then the reading and analysis of detailed documents can be used to assign the notion, the behavioral response, the attribute and the method of the recorded words. The eLEL construction process consists of thirteen steps based on the process proposed by [7,11,13]:…”
Section: Elel Building Processmentioning
confidence: 99%
“…The documents generated during this phase of elucidation (investigation reports, interviews, regulation or related text and other sources of information systems) are written in natural language. These documents contain the terms in the domain of the problem which are the terms used by customers and users [11,13]. These documents are then used by relevant professionals, considering that professionals sometimes have different roles and participate with their skills in this process.…”
Section: Introductionmentioning
confidence: 99%
“…In the direction of making multidimensional modeling accessible to endusers with no knowledge of the multidimensional model and of bridging the terminological gap between end-users and designers, this paper proposes a novel approach that creates a multidimensional schema from the language of the domain captured through a Language Extended Lexicon (LEL). LELs were introduced in the 90's as a technique to capture and describe the language used in the application domain (Universe of Discourse) [6] [7] [8] [9]. A LEL is a glossary whose goal is to record the definition of terms that belong to a domain.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the lexicon is not a simple requirement for the quality of a process, but it is also a source of reference for stakeholders. In [5,11,15] found that the lexicon (LEL) like ontology represents only the overall view of a system, and does not allow stakeholders to represent the detailed conceptual level of the system. In addition, properties or features of every concept are combined in the notion or in the behavioral response of the LEL symbol.…”
Section: Introductionmentioning
confidence: 99%